Genetic Analysis of Children With Unexplained Developmental Delay and/or Intellectual Disability by Whole-Exome Sequencing - Xiang, Jingjing; Ding, Yang; Yang, Fei; Gao, Ang; Zhang, Wei; Tang, Hui; Mao, Jun; He, Quanze; Zhang, Qin; Wang, Ting (Frontiers in Genetics, 2021)
Background: Whole exome sequencing (WES) has been recommended as a first-tier clinical diagnostic test for individuals with neurodevelopmental disorders (NDDs). We aimed to identify the genetic causes of 17 children with developmental delay (DD) and/or intellectual disability (ID). Methods: WES and exome-based copy number variation (CNV) analysis were performed for 17 patients with unexplained DD/ID. Results: Single-nucleotide variant (SNV)/ small insertion or deletion (Indel) analysis and exome-based CNV calling yielded an overall diagnostic rate of 58.8% (10/17), of which diagnostic SNVs/Indels accounted for 41.2% (7/17) and diagnostic CNVs accounted for 17.6% (3/17). Conclusions: Our findings expand the known mutation spectrum of genes related to DD/ID, and indicate that exome-based CNV analysis could improve the diagnostic yield of patients with DD/ID.